2010
DOI: 10.1358/mf.2010.32.5.1498327
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of gene transfection reagents in NG108-15, SH-SY5Y and CHO-K1 cell lines

Abstract: Several gene delivery reagents were analyzed for their transfection efficiency. Genes studied belonged to the class of mammalian proteins termed regulators of G-protein signaling (RGS), ranged in size up to 2.2 Kb long and were transfected into the NG108-15, SH-SY5Y and CHO-K1 cell lines. Prior to transfection, genes were cloned into a nonviral vector pcDNA 6.2/EmGFP, so as to express a green fluorescent protein tag at the 3' end. Flow cytometry was used to analyze cell fluorescent activity and thereby transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 19 publications
6
9
0
Order By: Relevance
“…Lipofectamine™-2000 served as a positive control for this experiment, since use of this lipid-based transfection agent is common. In the present study, a transfection efficiency of 10%–20% was observed for Lipofectamine™-2000 (see Figure 2 ), which is comparable to the findings of other researchers who reported undifferentiated SH-SY5Y cell transfection efficiencies ranging from 0.3%–4% [ 27 , 28 ]. Furthermore, the superior performance of the nanoparticle vectors, in particular Neuromag, is revealed when compared to the established Lipofectamine™-2000 control (see Figure 2 ).…”
Section: Resultssupporting
confidence: 91%
“…Lipofectamine™-2000 served as a positive control for this experiment, since use of this lipid-based transfection agent is common. In the present study, a transfection efficiency of 10%–20% was observed for Lipofectamine™-2000 (see Figure 2 ), which is comparable to the findings of other researchers who reported undifferentiated SH-SY5Y cell transfection efficiencies ranging from 0.3%–4% [ 27 , 28 ]. Furthermore, the superior performance of the nanoparticle vectors, in particular Neuromag, is revealed when compared to the established Lipofectamine™-2000 control (see Figure 2 ).…”
Section: Resultssupporting
confidence: 91%
“…These fi ndings are consistent with other studies on cytotoxicity effect of Turbofect (8). Although there are many reports about the cellular toxicity of Lipofectamine 2000 in comparison with other transection reagents such as Turbofect, there are just few published studies on toxicity of Lipofectamine 3000 (9,19,(20)(21)(22)(23). In one study, Lipofectamine CRISPRMAX was compared with Lipofectamine 3000 and Lipofectamine RNAiMAX, and signifi cant effi ciency with less toxicity of Lipofectamine CRISPRMAX was shown (12,(23)(24)(25)(26).…”
Section: Discussionsupporting
confidence: 80%
“…The e ciency of DNA electroporation varied from about 60% for CHO-K1 to 20% for SH-SY5Y. These outcomes are comparable with previous results using lipidic transfecting agents for the delivery of a non-viral expression vector, where the high e ciency of CHO-K1 transfection (60-80%) was drastically reduced to 5% for SH-SY5Y cells [44]. Our experiments, besides demonstrating an improved e ciency for SH-SY5Y cells, paved the way for the use of in-situ capacitive electroporation for serial gene transfection of cells in adhesion.…”
Section: Discussionsupporting
confidence: 84%